Estudo comparativo de perdas técnicas em redes de distribuição: análise entre diferentes considerações de modelagem dos elementos da rede utilizando o OpenDSS - Lopes, João Paulo Monteiro (2023)
The present work aims to carry out a comparative study of technical losses in a Medium Voltage power distribution system, using the OpenDss software, on the CCA01C3 feeder located in Caucaia and immediately adjacent regions. As is known, ANEEL has sought to improve the method for calculating distribution losses with the aim of not only supporting the determination of the level of losses (technical and non-technical) but also standardizing the calculation procedure and reducing asymmetry. The actual feeder data was made available by ENEL Ceará with the identification of elements such as lines, transformers, disconnecting switches, voltage regulators and capacitor banks. Furthermore, the BDGD database was used, with the help of QGIS software, to analyze the feeder data. Based on the OpenDss simulation, two comparative models were adopted: the first was based on the calculation methodology with positive sequence impedance (R1 and X1), stipulated by ANEEL. At this stage, the simulation included the insertion of a capacitor bank, voltage regulator and grounding resistances; the second model, in turn, was based on the geometry of the conductors, in which two structures of the Medium Voltage overhead network of conductors were analyzed, N1 and B1, whose evaluation considered the losses separately and together. From the simulations implemented, considering the insertion of elements to regulate the voltage profile and power factor and the comparison with the second model, it was found that the level of technical losses was relatively close, varying from 3.64 to 6.51%. Therefore, in this comparative study, modeling line parameters using positive sequence impedance represented a more effective model for calculating technical losses.